Pengaruh Dosis Pupuk Bokashi Limbah Ampas Tahu dan Fosfat terhadap Komponen Produksi Tanaman Kacang Tanah (Arachis hypogaea L.) - Venni Astuti; Laode Afa; Norma Arif (LP3M Universitas Muhammadiyah Kendari, 2022)
The combination of organic and inorganic fertilizers can increase the productivity of peanuts. The research aims to determine the effect of the dosage of bokashi tofu dregs waste and phosphate fertilizer on the yield component. The research design used was a factorial arranged in a Randomized Block Design. The first factor was tofu dregs waste bokashi dose treatment (K) consisting of four levels, i.e. without bokashi of tofu dregs waste (K0); 5 tons per hectare (K1), 10 tons per hectare (K2), 15 tons per hectare (K3); and second factors were phosphate fertilizer dosage (P) consisting of three levels, namely without phosphate (S0); 100 kg per hectare (S1); 200 kg per hectare (S2). Each experimental unit was repeated three times. The analysis of data on the number of young poods per plant, number of pithy seeds weight per plant and weight of 100 seeds using ANOVA if the analysis result of significant (Fhit> Ftab), then continue with DMRT test on α=0.05. The results showed that treating tofu dregs waste bokashi 15 tons per hectare and phosphate 200 kg per hectare can improve the yield components.